Synergistic enhancement in mechanical properties of graphene/MWCNT reinforced Polyaryletherketone – carbon fiber multi-scale composites: Experimental studies and finite element analysis - Sarath Kumar Painkal; Meera Balachandran; Karingamanna Jayanarayanan; Nagaarjun Sridhar; Sanjeev Kumar (Advanced Industrial and Engineering Polymer Research)
This investigation focuses on the synergistic performance improvement in graphene/MWCNT reinforced Polyaryletherketone (PAEK) - carbon fiber (CF) multi-scale composites. FTIR revealed the chemical interactions while HRTEM, XRD and 3D X-ray microscopy gave insight into nanofiller dispersion and microstructural features. The functional groups on nanofillers along with structural features integrated various components of the multi-scale composites by formation of graphene/MWCNT/CF complex network that provided larger interfacial area, bridging effect and physico-chemical interaction with PAEK while restricting its segmental mobility. Multi-scale composites displayed significantly improved strength, fracture toughness, interlaminar shear strength, glass transition temperature and tribological performance. Under dynamic load, graphene/MWCNT reinforcement of matrix and CF synergistically increases the storage modulus and energy absorption characteristics. Wear and fracture surface morphology of nano and multi-scale composites showed ductile failure confirming interfacial adhesion. The failure behavior in experimental studies was supported by Abaqus/Explicit-based FEM models of fracture toughness response. This work provides a promising avenue to develop next generation high performance thermoplastic composites for structural applications.